Socio-Psychological Factors Influencing the Choice of Teaching as a Career: A Study of Post Graduate Students in Delhi - Sirohi, Vineeta (INDIAN EDUCATIONAL REVIEW, 2011)
This study responds to the current challenge of inadequate supply of teachers in Indian higher education. The present study is an attempt to ascertain the choice of post graduate students for teaching and explore the factors influencing the choice of teaching as a career in higher education. A survey was carried out on a sample of 303 post graduate final year students selected through a multistage stratified sampling technique. Results revealed that approximately one-third of the students were inclined towards teaching profession. A significant difference was found between academic stream and inclination towards teaching. Further, significant differences were also found across professions in terms of job preference, economic benefit, freedom of work and job security. While, career choice of teaching was found to be influenced by various socio-psychological factors, no evidence was adduced to support gender influence. The findings have implications for policy makers and educationists for attracting and retaining talent in teaching profession.